The global targeting of education and skill: policy history and comparative perspectives. Issue 6 (1st November 2016) - King, Kenneth
Abstract : This analysis covers the period from 1925 to 2016 in respect of constructing national and global goals and targets in education and training. Tensions between global and national approaches to target-setting are identified. Equally, the ownership of the global target discourse is discussed along with its contested relevance to both developed and developing economies. The process of constructing Sustainable Development Goal 4 (on Education) is laid out against a background of this essential history. The milestones in this process include national initiatives on education for all in India and China, the Universal Declaration of Human Rights, the UNESCO regional conferences on education, the world conferences on education in Jomtien, Dakar and Incheon, and the UN's Open Working Group on Sustainable Development Goals. Across these and several other staging posts, the actual texts and framing of the goals and targets are subjected to critical review.